2018
DOI: 10.2490/prm.20180015
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Japanese Version of the Mini-balance Evaluation Systems Test in Patients with Subacute Stroke

Abstract: The objective of the current study was to evaluate the reliability and validity of the Japanese version of the Mini-Balance Evaluation Systems Test (J-Mini-BESTest) in patients with subacute stroke. Methods: Eighteen patients who had suffered a first hemiplegic stroke (mean age, 59.1 ± 27.0 years) and had been admitted to convalescent rehabilitation wards were enrolled. The J-Mini-BESTest, the Berg Balance Scale (BBS), and the functional reach test (FRT) were used to assess balance. Four physical therapists (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…The weighted kappa statistics for single item agreement have not been elicited for item 1 (sit to stand) and item 7 (stand on a firm surface), which may be due to the fact that similarly high scores were given by both raters at both times for all participants. This explanation is consistent with the results of a previous study in which almost perfect scores in these items from all raters were reported, as well as with the finding that these results were likely to be influenced by the ease of the task [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…The weighted kappa statistics for single item agreement have not been elicited for item 1 (sit to stand) and item 7 (stand on a firm surface), which may be due to the fact that similarly high scores were given by both raters at both times for all participants. This explanation is consistent with the results of a previous study in which almost perfect scores in these items from all raters were reported, as well as with the finding that these results were likely to be influenced by the ease of the task [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…As a result, we conclude that the Mini-BESTest can be used in the BVP population, as has been shown with other patient populations such as people with balance disorders, 49 , Parkinson's disease, 50,52 chronic stroke 51 and subacute stroke. 53 While feasible, there is currently no data on the reliability of the Mini-BESTest in the BVP population, which future work should address.…”
Section: Discussionmentioning
confidence: 99%
“…Also, other indicators related to CRF, including FRT and BBS were worse in patients with stroke. FRT and BBS are widely used as assessment tools for both static and dynamic balance in clinical settings ( 67 ). The balance represents the ability to control the center of mass concerning the base of support ( 68 ).…”
Section: Discussionmentioning
confidence: 99%